Gradual Internationalization vs Born-Global/International new venture models: A review and research agenda. Issue 6 (11th November 2019) - Paul, Justin; Rosado-Serrano, Alexander
Abstract : Purpose: During the last two decades, studies on the theoretical models in the area of international business (IB), such as gradual internationalization and the born-global firms, have gained the attention of researchers. The purpose of this paper is to critically review the studies on the process of internationalization (Gradual Internationalization vs Born-Global/International new venture models) to identify the research gaps in this area and to prepare a future research agenda. Design/methodology/approach: Systematic literature review method was employed for this review. The authors highlight the findings from prior studies, compare and contrast salient characteristics and features, based on the articles published in journals with an impact factor score of at least 1.0, and provide directions for research. Findings: The authors find that there are several areas that were under-explored in prior research. There is a great potential for theoretical extension and theory development in this field as it covers the tenets of four subjects: IB, marketing, strategic management and entrepreneurship. Originality/value: There is no comprehensive/integrated review exploring the methods/variables and constructs used in prior studies integrating gradual internationalization/born-global models based on all the articles published in well-regarded academic journals. This review seeks to provide deeper insights, which help us to contribute toward the development of this research field.